EVALUATING FUNGI INDOOR PRESENCE IN HOMES THROUGH VIABLE AND NON-VIABLE SAMPLING - Fernández Rodríguez, Santiago; Maya Manzano, José María; Ortega Garrido, Alfonso; de Tena Pascual, Diego; Silva Palacios, Inmaculada; Gonzalo Garijo, Ángela; Tormo Molina, Rafael (Boletín Micológico, 2011)
Moulds are common and important allergens. They are more abundant outdoors but patients affected by mould allergy stay indoors much longer than outdoors. So, indoor sampling could help to assess the influence of the concentration of allergens in allergic symptoms. The aim of this study was to assess the relative efficiencies of two air sampling methods, viable and non viable, for the quantification of airborne indoor fungi in the homes of patients sensitized to Alternaria. Furthermore, outdoor sampling was carried out to compare results. Samples were taken over six months in Badajoz (SW Spain). Two houses were selected according to the presence of allergic patients to Alternaria. They were sampled once a month using both viable and non viable personal samplers at solar noon. A Burkard personal sampler was used to record spores and a Sampl’air AES Chemunex sampler was used for colonies. Three rooms were selected in each home: living room, kitchen and bathroom. Temperature and relative humidity were registered at each sample. Outdoor sampling was performed one day per week at the Faculty of Science, using a seven day Burkard sampler for spores and the same personal sampler for colonies. On average, 200-300 CFU/ m3 were found from more than 40 taxa identified. The highest number of colonies was recorded in the kitchen, then in the bathroom and finally in the living room. Nevertheless, there were minor differences between rooms. The houses studied showed a similar temporal pattern, with maximum values in December and minimum in January. Cladosporium colonies showed statistical differences between homes, but these differences were not found with Alternaria, Aspergillus or Penicillium colonies. Differences between rooms appeared for Alternaria colonies and Cladosporium herbarium spores. Temperature was positively correlated in most cases and relative humidity negatively with Alternaria spores. The number of spores collected was as twice as that of colonies, with an average concentration between 600-700 colonies/m3 , and nearly 1400 spores/m3 as maximum concentration. The temporal pattern of spores was similar to that found for colonies. Comparing colonies to spores, Alternaria and AspergillusPenicillium showed similar values. Notwithstanding, Cladosporium spores were nearly five times more abundant than colonies. The advantage of viable methods is the identification to species level, but they have the disadvantage that spores from some ubiquitous species, as Cladosporium, do not always grow in those media, which raises the interest to use additional non-viable methods.